Quantitative Model in Security Informatics Risk Assessment (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2016)
This paper shows the importance of approaching in security Risk Assessment (RA) about Quantitative model in Risk Management. The RA has been calculated with qualitative method by different framework, for example: RISK IT FRAMEWORK (COBIT Component) [7], OCTAVE – ALLEGRO [8], MAGERIT V3 [9], FAIR [4], ISO 27005 [11], NIST800-30 [3]. All frameworks included in the scope the Risk Assessment; however this is more qualitative than quantitative. In this work, we propose a methodology to support the implementation and execution risk management, using quantitative risk assessment method. The methodology is based on three components: secure capture logs (apply networks forensic technical), likelihood risk or log analysis with logistic regression and risk assessment with influence diagrams.
Keywords: Risk Assessment; Information security; logistic regression statistics model; influence diagrams; IDS; Network forensic